A force-insensitive impedance compensation method for giant magnetostriction ultrasonic cutting system of Nomex honeycomb composites. (15th August 2022) - Ma, Ke; Wang, JianJian; Zhang, Jianfu; Feng, Pingfa; Yu, Dingwen; Ahmad, Shahzad
Abstract: The high-quality machining of Nomex honeycomb composites is challenging due to its intrinsic brittleness. The rotary ultrasonic cutting performed on Giant magnetostriction ultrasonic system (GMUS) has been recognized as a superior method for the high-quality machining of Nomex honeycomb, owing to its capability to generate large-amplitude ultrasonic tool vibration. The stability of ultrasonic tool vibration plays a critical role in guaranteeing the acceptable surface quality of Nomex workpiece. However, the unique inhomogeneity of honeycomb induces time-varying cutting force, which can violate the stability of ultrasonic tool vibration using conventional compensation methods. In this study, a force-insensitive impedance compensation (FIC) method was proposed to improve the vibration stability of GMUS for honeycomb machining. A theoretical model which describes the vibration characteristics of GMUS was developed to calculate the optimum compensation impedance to adapt the time-varying cutting force. Experimental tests were conducted on Nomex honeycomb composite to evaluate the performance of proposed FIC method by inspecting the surface quality of machined workpiece. The experimental results demonstrated that the compensated ultrasonic cutting system showed an enhanced vibration stability during the machining of Nomex honeycomb composite. Compared with conventional compensation method, the honeycomb processed by GMUS with the FIC method showed much fewer cell collapses.